Hubungan Infeksi Gardnerella vaginalis Dengan Manifestasi Klinis Keputian Penyebab Vaginosis Bakterialis Pada Ibu Hamil Ketuban Pecah Dini Di RSUP Dr. M. Djamil Padang - Fitri Anggraini; Andani Eka Putra; Vaulinne Basyir (BEST Journal (Biology Education, Sains and Technology), 2025)
Premature rupture of membrane (PROM) is one of the abnormalities found in pregnancy. The results find out that Lactobacillus is associated with the reduced risk of premature rupture of membrane (PROM), while Gardnerella, Prevotella, Megasphaera, Ureaplasma and Dialister are associated with the increase risk of PROM. Gardnerella vaginalis, a facultative anaerobic bacterium, is the most common microbe associated with bacterial vaginosis (BV).The research used cross sectional research design with retrospective data collection method. The research included all vaginal swab samples from pregnant women with premature rupture of membranes at RSUP Dr. M. Djamil, Padang. The sampling technique used was consecutive sampling, with 31 samples from pregnant women who experienced premature rupture of membranes, complemented with data from electronic/manual medical records. Clinical data collected included complaints such as vaginal discharge. The microbes that cause bacterial vaginosis were examined using Real-Time PCR at the PDRPI Laboratory, Faculty of Medicine, Universitas Andalas. Data then were analyzed using the chi-square test, followed by calculation of the Odds Ratio (OR).he results showed no significant association between the presence of G. Vaginalis and vaginal discharge (p = 0.384; OR = 2.67), Based on the analysis, most bacterial vaginosis infections occurred without the evident of clinical manifestations (asymptomatic) which caused to delayed diagnosis and an increased likelihood of cases being inadequately managed.The conclusion of this research shows that there is no significant association between microbes of bacterial vaginosis and manifestation of vaginal discharge in pregnant women. Antenatal care (ANC) interventions should include the development of a routine vaginal infection screening system within ANC services. Keywords: Gardnerella vaginalis, Bacterial Vaginosis, Pregnant Women